Sequence of an influenza virus hemagglutinin determined directly from a clinical sample. - Rajakumar, A (1990)
The sequence of the HA1 region of the hemagglutinin gene of an influenza virus has been determined without growing the virus in eggs or in cultured cells. The virus used was an H1 strain of influenza A from a clinical specimen taken from a patient in 1987. RNA was extracted directly from virus that had been sedimented out of the transport medium in which the sample had been stored. DNA copies of the hemagglutinin gene, obtained by reverse transcription, were then amplified by the polymerase chain reaction and were sequenced by the dideoxy termination method. The deduced amino acid sequence is highly similar to that of other H1 viruses that had been isolated at about the same time and cultured for a limited number of passages in eggs. Furthermore, the HA1 sequence of progeny virus from this isolate obtained after one passage in chicken embryos is identical to that of the virus obtained directly from the nasopharynx. The results suggest that H1 isolates that have been grown for a limited number of passages in embryonated eggs have HA1 subunits that faithfully represent the virus population in the clinical samples from which they were derived.